2022
DOI: 10.1177/11206721221083799
|View full text |Cite
|
Sign up to set email alerts
|

Double safe suture during cataract surgery on post radial keratotomy patients using clear corneal incisions

Abstract: Purpose the aim of this study is to find a safer surgical approach in cataract surgery on eyes previously treated with radial keratotomy using clear corneal incisions. Setting Department of Biomedical and Dental Sciences and Morphofunctional Imaging, Ophthalmology Clinic, University of Messina, Messina, Italy. Design Prospective study. Methods A prospective study was conducted on a group of 20 patients, 21 eyes with 16 RK incisions were evaluated for cataract phacoemulsification. Samples were divided into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…For such less convenient conditions for an EDOF IOL consideration, Meduri et al suggested some perioperative methods such as stabilizing sutures that lowered the risk of dehiscence as well as the postoperative astigmatism [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For such less convenient conditions for an EDOF IOL consideration, Meduri et al suggested some perioperative methods such as stabilizing sutures that lowered the risk of dehiscence as well as the postoperative astigmatism [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in Singapore showed that myopia (<−0.5D) was closely related to increased incidence of nuclear cataract (OR = 4.99) and posterior subcapsular cataract (OR = 1.34) [ 24 ]. And cataract surgery is also made more difficult in patients who have previously underwent corneal refractive laser surgery, such as intraocular lens power calculation [ 25 , 26 ]. A recent meta-analysis showed a strong association with nuclear and posterior subcapsular cataract for any myopia, while cortical cataract tends to develop more in emmetropes and hyperopes than myopes [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…AL changes have been described after cataract surgery too ( 33 ), but in this case, the reason could be the lens extraction, which causes a decrease in the eye volume. Other unexpected changes can be detected in case of RK, where the presence of deep cuts, can induce corneal dehiscence during phacoemulsification that can change the anterior segment morphology ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%